2007
DOI: 10.1093/ajcn/85.6.1643
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with overweight in preschool-age children in southwestern France

Abstract: A family history of overweight or diabetes, overweight in the first 2 y of life, and television viewing are associated with overweight at 4 y. These factors should be considered in developing programs for the prevention of overweight in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
3
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 31 publications
13
72
3
8
Order By: Relevance
“…The absence of this association may be due to the construction of the variable, which considered only the intake of certain chosen foods groups of interest -not from a complete FFQ; or it may be due to under-reporting of the consumption of unhealthy foods by the mothers (32) , which might have influenced or masked an association with overweight. Many studies have reported a positive association between being overweight and the amount of time spent watching television (15,33,34) . This is likely because children who watch television for more than an hour daily tend to participate less in sports and other physical activities, therefore being more inactive than children who watch less television (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of this association may be due to the construction of the variable, which considered only the intake of certain chosen foods groups of interest -not from a complete FFQ; or it may be due to under-reporting of the consumption of unhealthy foods by the mothers (32) , which might have influenced or masked an association with overweight. Many studies have reported a positive association between being overweight and the amount of time spent watching television (15,33,34) . This is likely because children who watch television for more than an hour daily tend to participate less in sports and other physical activities, therefore being more inactive than children who watch less television (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Children underwent a medical visit whereby anthropometric measurements were taken by the study physician. 23 Weight was determined for children in minimal clothing without shoes to the nearest 0.5 kg using a Seca scale (Hamburg, Germany), and height to the nearest 0.5 cm with a stadiometer fixed to the wall (Seca) using standardized techniques. Children were classified by the study physician using French reference curves for BMI; 24 those with BMI value between 75th and 90th percentiles (z-score between 0.67 and 1.28) were considered at risk for overweight and those with BMI X90th percentile (z-score X1.28) were considered overweight.…”
Section: Methodsmentioning
confidence: 99%
“…For the current review, four eligible and new crosssectional studies were identified ( Table 2). The focus of three of these four studies (86)(87)(88) was parent-reported television viewing and significant associations with overweight and/or obesity, usually robust to a range of adjustments, were found. In the fourth (89) , which was a small study, significantly lower risk of overweight and obesity at higher levels of physical activity was reported.…”
Section: Evidence From Recent Cross-sectional Observational Studiesmentioning
confidence: 99%